Efektifitas Pendristibusian Zakat Pertanian dalam Meningkatkan Kesejahteraan Masyarakat Miskin di Jorong Supanjang, Kabupaten Tanah Datar - Suhatri Mariko (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem of this research is the method of distributing agricultural zakat in improving the welfare of the poor in Jorong Supanjang Nagari Cubadak, Lima Kaum District. The purpose of this discussion is to find out and analyze the effectiveness of the Zakat Distribution Method for agricultural products in improving the economic welfare of the poor. The type of research that the authors use is field research with a qualitative descriptive approach. Data collection techniques are by observation, interviews and documentation. The results of the study found that the method of distributing agricultural zakat was carried out using the traditional consumptive pattern, namely giving zakat in the form of money to Mustahiq at the time of the rice harvest thanksgiving prayer (Prayer is already reaped) and by giving it directly to mustahiq without going through an activity or thanksgiving prayer. Zakat is paid once a year with the amount of zakat ranging from IDR 1,000,000 to IDR. 1,500,000.- Then the amount of zakat received by Mustahiq for one activity ranges from Rp.50,000 to Rp.100,000.-. Based on data on the amount of zakat funds distributed and then compared with the number of poor people in Jorong Supanjang, the method used in distributing agricultural zakat has not been effective and has not been able to prosper the poor or Mustahiq.